Simultaneous determination of five common additives in insulating mineral oils by high‐performance liquid chromatography with ultraviolet and coulometric detection. Issue 15 (12th July 2016) - Bruzzoniti, Maria Concetta; Sarzanini, Corrado; Rivoira, Luca; Tumiatti, Vander; Maina, Riccardo
Abstract : Dielectric mineral oils are used to impregnate power transformers and large electrical apparatus, acting as both liquid insulation and heat dissipation media. Antioxidants and passivators are frequently added to mineral oils to enhance oxidation stability and reduce the electrostatic charging tendency, respectively. Since existing standard test methods only allow analysis of individual additives, new approaches are needed for the detection of mixtures. For the first time we investigate and discuss the performance of analytical methods, which require or do not require extraction as sample pretreatment, for the simultaneous reversed‐phase high‐performance liquid chromatography determination of passivators (benzotriazole, Irgamet ® 39) and antioxidants ( N ‐phenyl‐1‐naphtylamine, 2, 6‐di‐ tert ‐butylphenol, 2, 6‐di‐ tert ‐butyl‐ p ‐cresol), chosen for their presence in marketed oils. Quick easy, cheap, effective, rugged and safe and solid phase extractions were evaluated as sample pretreatments. Direct sample‐injection was also studied. Ultraviolet spectrophotometry and direct‐current coulometry detection were explored. As less prone to additive concentrations variability, the direct‐injection high‐performance liquid chromatography with ultraviolet and coulometric detection method was validated through comparison with Standard Method IEC 60666 and through an ASTM interlaboratory proficiency test. Obtained detection limits are (mg kg −1 ): benzotriazole (2.8), Irgamet ® 39 (13.8), N ‐phenyl‐1‐naphtylamine (11.9), 2, 6‐di‐ tert ‐butylphenol (13.1), 2, 6‐di‐ tert ‐butyl‐ p ‐cresol (10.2). Simultaneous determination of selected additives was possible both in unused and used oils, with good precision and accuracy.